Implementation of Application Based Audits to Increase Auditor Effectiveness in Detecting Fraud - Dewi Saptantinah Puji Astuti; Abeta Betriyana (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Fraud in the business world is a major problem that can undermine auditor credibility and reduce the quality of financial reports. Auditors are required to be able to detect indications of fraud more accurately, but the limitations of traditional methods often make fraud detection less than optimal. Digital transformation in audit practice, through the implementation of simple applications, presents new opportunities. This study aims to analyze the role of application-based auditing on auditor effectiveness in detecting fraud. Primary data was obtained from 60 auditors from Public Accounting Firms (KAP) in Central Java with a minimum experience of three years. Data analysis was conducted using descriptive statistics, instrument testing, classical assumption tests, and simple linear regression. The results show that the application of application-based auditing has a positive and significant effect on auditor effectiveness in detecting fraud. This study emphasizes the importance of utilizing digital audit technology to improve audit quality. Recommendations for further research include expanding the audit sample by expanding the research area and adding variables such as auditor competence, ethics, and independence.